A pathogen‐derived metabolite induces microglial activation via odorant receptors. (21st February 2020) - Lee, NaHye; Jae, YoonGyu; Kim, Minhyung; Cho, TaeHo; Lee, ChaeEun; Hong, Yu Ri; Hyeon, Do Young; Ahn, Sanghyun; Kwon, Hongmok; Kim, Kyul; Jung, Jae Hoon; Chae, Sehyun; et al.
Abstract : Microglia (MG), the principal neuroimmune sentinels in the brain, continuously sense changes in their environment and respond to invading pathogens, toxins, and cellular debris, thereby affecting neuroinflammation. Microbial pathogens produce small metabolites that influence neuroinflammation, but the molecular mechanisms that determine whether pathogen‐derived small metabolites affect microglial activation of neuroinflammation remain to be elucidated. We hypothesized that odorant receptors (ORs), the largest subfamily of G protein‐coupled receptors, are involved in microglial activation by pathogen‐derived small metabolites. We found that MG express high levels of two mouse ORs, Olfr110 and Olfr111, which recognize a pathogenic metabolite, 2‐pentylfuran, secreted by Streptococcus pneumoniae . These interactions activate MG to engage in chemotaxis, cytokine production, phagocytosis, and reactive oxygen species generation. These effects were mediated through the Gαs –cyclic adenosine monophosphate–protein kinase A–extracellular signal‐regulated kinase and Gβγ –phospholipase C–Ca 2+ pathways. Taken together, our results reveal a novel interplay between the pathogen‐derived metabolite and ORs, which has major implications for our understanding of microglial activation by pathogen recognition. Database: Model data are available in the PMDB database under the accession number PM0082389. Abstract : Streptococcus pneumoniae is the most common causative pathogen of meningitis and induces brain inflammatory responses through microglial activation. Here, 2‐pentylfuran, secreted by S. pneumoniae, is identified; it interacts with microglial odorant receptors, Olfr110 and Olfr111, and induces microglial activation, including chemotaxis, cytokine production, phagocytosis, and reactive oxygen species generation. A novel interplay between the pathogenic metabolite and odorant receptor implicates an alternative sensing strategy of microglia for pathogenic infection.